2018
DOI: 10.1016/j.celrep.2018.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Modular Study of the Type III Effector Repertoire in Pseudomonas syringae pv. tomato DC3000 Reveals a Matrix of Effector Interplay in Pathogenesis

Abstract: The bacterial pathogen Pseudomonas syringae pv. tomato DC3000 suppresses the two-tiered innate immune system of Nicotiana benthamiana and other plants by injecting a complex repertoire of type III secretion effector (T3E) proteins. Effectorless polymutant DC3000D36E was used with a modularized system for native delivery of the 29 DC3000 T3Es singly and in pairs. Assays of the performance of this T3E library in N. benthamiana leaves revealed a matrix of T3E interplay, with six T3Es eliciting death and eight oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 30 publications
(67 reference statements)
4
69
0
Order By: Relevance
“…It has been reported that P. syringae pv. tomato DC3000 possesses several type III effectors that can suppress HopQ1‐triggered HR cell death (Wei et al , ; Zembek et al , ). GMI1000 might possess effectors that suppress RipB‐triggered ETI responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that P. syringae pv. tomato DC3000 possesses several type III effectors that can suppress HopQ1‐triggered HR cell death (Wei et al , ; Zembek et al , ). GMI1000 might possess effectors that suppress RipB‐triggered ETI responses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Arabidopsis accession Col-0 (Col) is resistant to Pst bacteria translocating AvrRpt2, recognized by the CNL RPS2 (Bent et al, 1994;Mindrinos et al, 1994), but resistance is impaired in lines lacking EDS1 and the defense-associated hormone salicylic acid (SA; Venugopal et al, 2009;Vlot et al, 2009;Cui et al, 2017). However, Pst assumingly translocates up to 29 different effectors into host plants (Wei et al, 2015;Wei et al, 2018), and infection assays fail to detect weak recognition events in interactions termed 'compatible'. Indeed, basal resistance is also impaired in lines lacking RAR1 or SGT1 (required for maturation and accumulation of NLRs (Kadota et al, 2010;Zhang et al, 2010)), supporting the occurrence of weak recognition in the Pst DC3000 -Col interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of DC3000, which is a widely-used strain of Pst , is 6.5 Mb and encodes 5,763 ORFs (Buell et al ., 2003). In addition to 36 type III effectors (T3Es), which contribute to Pst virulence, DC3000 also produces a phytotoxin, coronatine (COR) that induces chlorosis and functions as a jasmonic acid-isoleucine mimic to promote colonization of plants by opening stomata and altering defense signaling pathways (Worley et al ., 2013; Sakatos et al ., 2018; Wei et al ., 2018). By deleting 28 well-expressed T3Es and then reintroducing combinations of multiple effectors back into DC3000, eight effectors were found to be required for near wild-type Pst growth in Nicotiana benthamiana (Cunnac et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%